Management of Physiotherapy in Post Stroke Patients Hemiparese Sinistra et Causa Non-Hemorrhagic with Infrared and Exercise Therapy - Didimus Budi Santoso; Boki Jaleha (Jurnal Indonesia Sosial Sains, 2024)
Stroke is a neurological deficit that occurs suddenly caused by a vascular disorder in the form of a lack of oxygen supply to the brain, resulting in damage or necrosis of brain tissue. Problems that arise in stroke sufferers include weakness on their side of the body, which causes balance disturbances until independence is reduced so that they will need the help of others. Therefore, the provision of infrared and exercise therapy interventions aims to increase muscle strength, improve body balance and restore functional activity ability. This study uses a case study approach, raises patient cases and collects data through the Physiotherapy process. The modalities provided are infrared and exercise therapy in the form of resisted exercise, CIMT, and bridging exercise. After 4 times of Physiotherapy, there was an increase in muscle strength. Still, there was no improvement in balance based on the Berg Balance Scale, and there was no increase in functional activity based on CAHAI and Barthel Index. Management of physiotherapy with infrared and exercise therapy carried out in the post-stroke hemiparese Sinistra et causa NonHemorrhagic for 4 times of therapy can increase muscle strength. Still, there has been no improvement in functional activity abilityDA.